Pengaruh Murottal Al-Quran Terhadap Tingkat Kecemasan Ibu bersalin di UPTD Puskesmas Padasuka - Farhani, Dini; Hidayanti, Desi; Wisnu Wardhani, Sri (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background : Labor pain is one of the most intense pains a woman will experience in childbirth. The pain felt by the delivery mother will have an anxiety effect on the mother. Based on the results of the study, the highest level of anxiety felt by birth mothers out of 50 respondents. 17 of them (34%) experienced moderate levels of anxiety, 13 people with normal levels of anxiety, 15 people with mild levels of anxiety and 5 people with severe levels of anxiety. Therefore, non-pharmacological therapy is needed to reduce anxiety in birth mothers, one of which is by using a distortion technique, namely listening to the Quran’s murottal. Method : This journal search method uses keywords, Boolean operators and E-data Based according to predetermined criteria. Purpose: to determine the influence of murottal Al-Quran on anxiety of mothers giving birth. Results: After being given the intervention, the mother's anxiety score decreased from 89 to 40 after listening to Murottal for 1.5 hours. Conclusion: There is an influence on the anxiety of mothers giving birth by being given Al-Quran murottal for 1.5 hours, namely reducing the level of anxiety of mothers giving birth.